The influence of residual stress on a roll forming process. (October 2015) - Abvabi, A.; Rolfe, B.; Hodgson, P.D.; Weiss, M.
Abstract: Roll forming is increasingly used in the automotive industry to form High Strength Steel (HSS) and Advanced High Strength Steel (AHSS) for structural components. Because of the large variety of applications of roll forming in the industry, Finite Element Analysis (FEA) is increasingly utilized for roll forming process design. Bending is the dominant deformation mode in roll forming and sheet materials used in the process are often temper rolled (skin passed), roller- or tension-levelled. These processes introduce residual stresses into the material, and recent studies have shown that those affect the material behaviour in bending. A thickness reduction rolling process available at Deakin that leads to material deformation similar to an industrial temper rolling operation was used in this study to introduce residual stresses into a dual phase, DP780, steel strip. The initial and thickness reduced strips were then used in a 5-stand experimental V-section roll forming set-up to identify the effect of residual stress on the final shape. The influence of residual stress and the effect of plastic deformation on the material behaviour in roll forming are separately determined in numerical simulation. The results show that the thickness reduction rolling process decreases the maximum bow height while the springback angle and end flare increase. Comparison with experimental results shows that using material data from the conventional tensile test in a numerical simulation does not allow for the accurate prediction of shape defects in a roll forming process if a residual stress profile exists in the material. On the other hand including the residual stress information leads to improved model accuracy. Highlights: Residual stresses were introduced in the material using a rolling process. The influence of residual stress on a roll forming process was investigated. Rolling increases springback and end flare in the component while bow is reduced. Including the residual stress information leads to improved model accuracy.